Evaluation of Drug Pricing Regulation Policies within Colombian Health Expenditure, 2010-2017. Issue 3 (3rd July 2022) - Espinosa, Oscar; Enríquez, Hernán; Ávila, Diego; Basto, Sergio; Rivera, Daniela; López, Daniela; Avellaneda, Paola; Riveros, Paola
Abstract: This research presents the impact assessment for medication price regulation policy in Colombia, having as a frame of reference the relevant markets and the Unique Code of Medicines (CUM) [Código Único de Medicamentos], regulated in the circulars 04, 05, 06, 07 of 2013, and 01 of 2014. After an interdisciplinary construction of a database with information between 2010 and 2017, a statistical model of dynamic difference-in-differences was estimated. Although the effect is momentary, the reduction of spending, as an objective of the policy, it is notorious. This behavior mainly occurs since most of the medicines included in regulation reflect monopoly prices, where the most significant reduction in prices was observed and, therefore, the most considerable expense restraint.